1997
DOI: 10.1080/026990597123601
|View full text |Cite
|
Sign up to set email alerts
|

Subject review with case study: Pseudotumour cerebri risk for cognitive impairment

Abstract: Does increased intracranial pressure in patients with pseudotumour cerebri (PTC) result in cognitive impairments? The results of previous investigations have not clarified this question. It may be that there is a subgroup within those diagnosed with PTC that does experience cognitive decline with increased intracranial pressure. However, elevated intracranial pressure, headache, and emotional distress also can contribute to reduced cognitive performance and increased self-monitoring. As a result of the lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…Cognitive function in IIH has only been reported in three studies2–4 in addition to a single case report 5. One study2 examined 85 patients but applied only a single memory test and the methodology was not described in details.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive function in IIH has only been reported in three studies2–4 in addition to a single case report 5. One study2 examined 85 patients but applied only a single memory test and the methodology was not described in details.…”
Section: Discussionmentioning
confidence: 99%
“…Except for a single memory test conducted in 85 patients,2 the cognitive function in IIH has only been tested in a few very small study populations 3–5. In all studies, apart from the case report by Kaplan et al ,5 testing revealed significant cognitive deficits in patients with IIH. Especially within verbal tests and memory, deficits have been demonstrated.…”
Section: Introductionmentioning
confidence: 88%
“…Recent studies have also demonstrated that patients suffering from IIH chronically may experience significant cognitive deficits that include impairments in memory and concentration (Kaplan, Miner, & McGregor, 1997). Recent studies have also shown that patients with IIH are more likely than age-and weight-matched controls to be depressed, have heightened levels of anxiety, and have a poorer quality of life (Daniels et al, 2007;Kesler, Mosek, Fithlicher, & Gidron, 2005;Kleinschmidt, Digre, & Hanover, 2000).…”
Section: Additional Aspects Of Iih Presentationmentioning
confidence: 97%
“…4 Headache, papilledema, enlargement of the blind spot and elevated CSF pressure are the most common clinical features associated with IH (Box 1). 5 A temporary episode of blindness may be a harbinger of impending visual loss, increasing the urgency of diagnosis and treatment. However, symptoms may be absent and papilledema may be discovered incidentally during examination.…”
mentioning
confidence: 99%
“…[6][7][8] Although the early clinical course of IH does not reliably predict whether vision loss will persist, poor visual outcome has been associated with significant obesity. [5][6][7] The risk of permanent visual sequelae underscores the importance of maintaining a high index of suspicion for symptoms and signs of IH in patients taking minocycline or other associated medications.…”
mentioning
confidence: 99%